2019
DOI: 10.26434/chemrxiv.8003507.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Dual Sensor Probe for the Sequential Detection of Copper(II) and Lactic Acid

Abstract: <p>Herein, we report<b> </b>a novel fluorescent probe for the sequential detection of Copper II (Cu<sup>2+</sup>) and lactic acid. The probe based on acyl-thiourea derivative, N-((6-methoxypyridin-2-yl)carbamothioyl)benzamide (<b>1</b>) was synthesized, and its application as dual sensor for Cu<sup>2+</sup> and lactic acid is reported. The dual detection by the probe is possible since <b>1 </b>formed complex with Cu<sup>2+ </sup>and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…9,10 Our group has been interested in studying the self-assembly of single amino acids, 11,12 peptides, 13-15 oligonucleotides 13 and heterocyclic molecules. [16][17][18][19][20][21][22][23][24] Following the work of Gazit and our own research interests we have reported formation of amyloid like toxic fibers by the selfassembly of cysteine and methionine. 11 We have also recently reported the formation of toxic aggregates formed by the self-assembly of proline and hydroxyproline.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Our group has been interested in studying the self-assembly of single amino acids, 11,12 peptides, 13-15 oligonucleotides 13 and heterocyclic molecules. [16][17][18][19][20][21][22][23][24] Following the work of Gazit and our own research interests we have reported formation of amyloid like toxic fibers by the selfassembly of cysteine and methionine. 11 We have also recently reported the formation of toxic aggregates formed by the self-assembly of proline and hydroxyproline.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Our group has been interested in studying the self-assembly of single amino acids, 11,12 peptides, 13-15 oligonucleotides 13 and heterocyclic molecules. [16][17][18][19][20][21][22][23][24] Following the work of Gazit and our own research interests we have reported formation of amyloid like toxic fibers by the selfassembly of cysteine and methionine. 11 We have also recently reported the formation of toxic aggregates formed by the self-assembly of proline and hydroxyproline.…”
Section: Introductionmentioning
confidence: 99%